PERSONALISATION OF INSTRUCTOR-STUDENT INTERACTIONS IN ONLINE TEACHING IN MALAYSIA, THE PHILIPPINES, INDIA AND INDONESIA - Su Hie, Ting; Soo See, Chai; Alma, Bangayan-Manera; J., Karthikeyan; Dila, Novita; Sya'baningrum, Prihhartini (KITE Digital Educational Solutions, 2025)
The study examined strategies for personalisation of instructor-student interactions in online teaching by lecturers in Malaysia, the Philippines, India and Indonesia. The study involved 401 college/university students who filled in an online questionnaire. Results on the usage of technologies for online learning showed that some students had inadequate data for online learning in the Philippines. There was more frequent use of smartphones for online learning in the Philippines and Indonesia, and more frequent use of laptops in India and Malaysia. When it came to how promptly lecturers responded to student queries, we found that they normally replied within the same day. Lecturers employed various strategies to personalise their online teaching, such as reminding students of assignment deadlines, replying in chat/discussion threads, using humour, facilitating student friendships and sharing personal experiences. However, they drew a line at posting photos, considering it to be inappropriate. Filipino lecturers were the most student-centric. They were the most frequent users of strategies for personalising instructor-student interactions, and also gave students more leeway in making suggestions on the delivery of academic content, as compared to lecturers from Malaysia, India and Indonesia. A cross-country analysis showed that Indonesian students had the most initiative to make contact with their lecturers, with Malaysian students leaving the responsibility to lecturers. The cross-country study indicates that from the students’ perspective, quick responses to their messages help foster a sense of connection and support, enhancing the relational aspect of online learning.